Qualidade física, fisiológica e sanitária de sementes de feijão-caupi (Vigna unguiculata L. Walp.) utilizadas no Rio Grande do Norte - Silva, Fernando Henrique Alves da (Universidade Federal Rural do Semi-Árido, 2015)
The objective of this paper was to evaluate the physical, physiological and sanitary quality of 40 samples of cowpea seeds (Vigna unguiculata L. Walp.), which 37 samples was from saved seeds reused by producers from Rio Grande do Norte and two varieties of basic seeds, being a batch of BRS Pujante and two lots of BRS Guariba. The experiments were conducted at the Seed Analysis Laboratory and Microbiology and Phytopathology of the Universidade Federaldo Semi-Árido (UFERSA), Mossoró, RN from November 2013 to August 2014. The design used was in randomized block design for field emergence and entirely randomized to the analyzes performed in the laboratory. The data were submitted to analysis of variance and for the comparisons of means it was used the Scott Knott test, at 5% probability. The percentage data were transformed to arc sin √x / 100. The software used was ASSISTAT 7.7. For the physical analyzes the hectoliter weight tests were performed, thousand seeds weight, purity and seeds from other crops, in addition to determining the moisture content of the seeds; for physiological analyzes, germination tests were applied, first count, field emergence, speed of emergence index, seedling dry matter, accelerated aging and electrical conductivity; and for the sanitary quality tests of infested seeds and frequency and incidence of microorganisms were performed. The initial moisture content of the seeds oscillated from 8.9 to 21.3%; the hectoliter weight varied from 163 to 206 kg/hL; while the thousand seeds weight was from 159 to 352 g. For physical seed purity, it was observed values from 97.1 to 100%, wherein 5% of the samples were outside the standard (98%). Regarding the presence of other seeds, 45% of the samples were contaminated by seeds of other crops of the same species. For the germination test, 97% of the samples were above the minimum established by the law (70%). In the field emergence test it was verified that 95% of the samples obtained superior result to the minimum required (70%). 40% of the samples obtained inferior results of seedling emergence to those observed for the basic seed samples (control). For the accelerated aging it was verified that (29%) of the samples showed inferior results of the controls. And, 27% of the samples presented the lowest electrical conductivities are statistically equal to Pujante control. For the sanitary analysis it was verified the frequency of Alternaria sp. (10%), Aspergillus sp. (60%), Bipolaris spp. (8%), Colletotrichum sp. (5%), Fusarium sp. (53%), Macrophomina sp. (60%), Penicillium sp. (13%), Pleurophagminum sp. (5%), Rhizopus sp. (73%), Rhizoctonia sp. (70%), Rhizobium sp. (100%) and Pantoea sp. (3%). The bean weevil (Callosobruchus maculatus) appeared in 94% of samples. Therefore, it was concluded that the commercial seeds of cowpea, produced in accordance with the technical production recommendations, present superior physical, physiological and sanitary attributes to the saved or own seeds. On the other hand, the saved or own seeds show to be inadequate for seeding and/or marketing due to the low physical, physiological and sanitary quality
Physical, physiological and sanitary quality of cowpea seeds (Vigna unguiculata L. Walp.) used in Rio Grande do Norte
Keywords: Beans - Cowpea; Seed - Commercial; germination; Feijão - Caupi; Semente - Comercial; Germinação; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA